Assessing the Suitability of Chinese Cabbage as an Alternative Host for Spodoptera frugiperda (Lepidoptera: Noctuidae). Issue 1 (28th November 2022) - Wu, Meng-Ling; Zhao, Hao-Yang; Liu, Tong-Xian; Pan, Ming-Zhen
Abstract: When the favored host of an herbivorous insect pest is absent, the availability of alternative host plants can maintain insect pest populations. Spodoptera frugiperda (Lepidoptera: Noctuidae) is a major invasive, polyphagous insect pest in China. To investigate the suitability of Chinese cabbage as an alternative host for S. frugiperda, oviposition preferences and life history traits were determined for S. frugiperda on Chinese cabbage, corn, and winter wheat over three generations. Results showed that S. frugiperda females preferred to lay their eggs on corn compared to winter wheat and Chinese cabbage. The survival rate of S. frugiperda decreased after switching from corn to Chinese cabbage, only 6% of individuals successfully pupated in the third generation. In addition, S. frugiperda reared on Chinese cabbage had lower pupal weight and fecundity. Winter wheat was a good host for S. frugiperda ; although the survival rate decreased when S. frugiperda switched from corn to winter wheat in the parental generation, the survival rate increased over the next two generations to be as high as those reared on corn. Chinese cabbage is not a good long-term host for S. frugiperda, but it could maintain the pest population for at least two generations when more suitable host plants are unavailable. These results will inform management strategies for S. frugiperda .